AN INTELLECTUAL APPROACH TO THE USE OF NEUROMARKETING IN PHYSICAL THERAPY AND REHABILITATION - Elif Egzi Tuhta; Prof. Dr.Ercumend Ersanli (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
This study examines in depth the potential use of neuromarketing in the field of physical therapy and rehabilitation and the possible effects of this use. Neuromarketing is an approach to analyze the conscious and unconscious decisions of individuals and aims to shape marketing strategies using psychological and neuroscientific data. In this context, the study focuses on developing various strategies for more effective delivery of services by taking advantage of the potential of neuromarketing in the health sector, especially in the field of physical therapy and rehabilitation. The article states that neuromarketing applications in this field can play an important role in terms of increasing individuals' commitment to treatment processes, accelerating recovery times and making treatment processes personalized. For example, by using neuromarketing techniques, patients' psychological states, attitudes towards treatment and motivation levels can be better understood. This understanding allows for more effective personalization of the treatment process and a stronger commitment to treatment can be created. In addition, treatment methods can be made more efficient by taking individual differences into account during the recovery process. However, the article emphasizes that this potential of neuromarketing should be used within an ethical framework and based on scientific foundations. Since the use of neuromarketing in the health field can target the unconscious processes of individuals, such an intervention should be implemented carefully and responsibly. It is stated that neuromarketing methods used in the treatment process should be implemented with transparency and ethical boundaries in order not to have a negative impact on the emotional and psychological well-being of patients. In conclusion, it is emphasized that neuromarketing has significant potential in the field of physical therapy and rehabilitation, but this potential should be used with ethical responsibilities, based on scientific foundations and considering the psychological and physiological well-being of individuals. Such an approach will both allow health professionals to provide more effective treatment and increase patients' commitment to the treatment process, helping them to achieve a faster and more efficient recovery process.